Jumping improves lower limbs bone mass and lean mass in elite jumpers - Trabelsi, H.; Elloumi, M.; Mrad, M.; Aouichaoui, C.; Chortane, S. G.; Cheour, I.; Tabka, Z. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The present study was designed to examine the influence of extreme impact loading induced by jump training on bone mineral density (BMD) and bone mineral content (BMC) in high level jumpers.